2020
DOI: 10.1186/s12910-020-0450-2
|View full text |Cite
|
Sign up to set email alerts
|

Addressing harm in moral case deliberation: the views and experiences of facilitators

Abstract: Background: In healthcare practice, care providers are confronted with decisions they have to make, directly affecting patients and inevitably harmful. These decisions are tragic by nature. This study investigates the role of Moral Case Deliberation (MCD) in dealing with tragic situations. In MCD, caregivers reflect on real-life dilemmas, involving a choice between two ethical claims, both resulting in moral damage and harm. One element of the reflection process is making explicit the harm involved in the choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Some methods of ethical reflection are based on what is morally right according to policies and laws (Schuchter & Heller, 2018), while other methods focus on how participants perceive and construct moral rightness where legal or ethical principles might be a part of the dialogue, but not necessarily (Molewijk et al, 2011). The latter approach, known as moral case deliberation, acknowledges emotions and can promote a better understanding of oneself and give emotional support like comfort and enhanced resilience (Molewijk et al, 2011; Spronk et al, 2020). This accords with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Some methods of ethical reflection are based on what is morally right according to policies and laws (Schuchter & Heller, 2018), while other methods focus on how participants perceive and construct moral rightness where legal or ethical principles might be a part of the dialogue, but not necessarily (Molewijk et al, 2011). The latter approach, known as moral case deliberation, acknowledges emotions and can promote a better understanding of oneself and give emotional support like comfort and enhanced resilience (Molewijk et al, 2011; Spronk et al, 2020). This accords with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that there is also a need for a proactive, broader, multidisciplinary decision-making process for complex euthanasia requests of PWADs, for instance supported by moral case deliberation (MCD). A recent study showed that addressing harm in MCD aids healthcare professionals in the task they are facing [36]. Giving GPs better access towards MCD would be a sensible policy as it may counteract polarization within the profession and society.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high response rate emphasizes GPs' high involvement in this topic, as other surveys among Dutch GPs mostly had much lower response rates (around 30%) [38][39][40]. The respondents are representative for the Dutch GP practice, as checked for age, gender and region [36].…”
Section: Strengths and Limitationsmentioning
confidence: 94%
“…A recent study showed that addressing harm in MCD aids healthcare professionals in the task they are facing. [34] Giving GPs better access towards MCD would be a sensible policy as it may counteract polarization within the profession and society. In our earlier study we also argued for creating awareness of the possibility to consult a spiritual care provider.…”
Section: Discussionmentioning
confidence: 99%